Application of Superman Songs In the Pop Rock Genre Goes to Reggae with Ensemble Format at SMAN 3 Padangpanjang - rizki, azkia ghaniya; Yonhendri, Yonhendri -; Emridawati, Emridawati -; Awerman, Awerman -; Anggara, Rama (Scoring: Journal of Film Music, 2025)
The research entitled "The Application of Superman Songs in the Pop Rock Goes to Reggae Genre with Ensemble Format at SMA N 3 Padangpanjang" aims to determine the ability of researchers in providing learning in the field of music to students of SMA N 3 Padangpanjang. Lagu Superman is arranged into a musical ensemble format with instruments such as bellyra, pianica, bass guitar, electric guitar, drumset, and vocals. The research method used is qualitative in the form of action research, where the researcher goes directly to the research site. In the research process, the researcher applied several supporting methods: demonstration, imitation, exercise, and evaluation. This research aims to show students' progress and knowledge in playing musical instruments and understanding music's tempo and dynamics. The results of the research and teaching were performed by the students of SMA N 3 Padang Panjang at the Hoeridjah Adam Performance Building, Indonesian Institute of the Arts, Padangpanjang.